Bifunctional cleavable probes for in situ multiplexed glycan detection and imaging using mass spectrometry. Issue 8 (7th January 2019) - Ma, Wen; Xu, Shuting; Nie, Honggang; Hu, Bingyang; Bai, Yu; Liu, Huwei
Abstract : In situ multiplexed detection and imaging of glycans is of great significance since they mediate a range of biological activities. Abstract : In situ analysis of glycans is of great significance since they mediate a range of biological activities. Aberrant changes of glycosylation are closely related to cancer onset and progression. In this work, bifunctional laser cleavable mass probes (LCMPs) were developed for in situ glycan detection from both cells and tissues using laser desorption ionization mass spectrometry (LDI-MS). Specific recognition of glycans was achieved by lectins, and inherent signal amplification was achieved by the conversion of the detection of glycans to that of mass tags which overcame the low ionization efficiency and complicated mass spectra of glycans. Multiplexed glycan profiling was easy to implement due to the simple and generic synthetic route to LCMPs and serial alternative mass tags, which offers high sensitivity, low interference and in situ detection of glycans. Moreover, as an excellent inherent matrix, LCMPs facilitated direct glycan detection from the cell surface and tissue imaging using LDI-MS. Intrinsic and fine glycan distribution in human cancer and paracancerous tissues was strictly demonstrated by MS imaging to explore the correlation between glycosylation and various cancers. This approach presented a versatile LDI-MS based platform for fast and in situ multiplexed glycan engineering, thus providing a new perspective in glycobiology and clinical diagnosis.